2011
DOI: 10.1002/cne.22733
|View full text |Cite
|
Sign up to set email alerts
|

Projections of the medial orbital and ventral orbital cortex in the rat

Abstract: The medial orbital (MO) and ventral orbital (VO) cortices are prominent divisions of the orbitomedial prefrontal cortex. To our knowledge, no previous report in the rat has comprehensively described the projections of MO and VO. By using the anterograde tracer Phaseolus vulgaris leucoagglutinin and the retrograde tracer Fluoro-Gold, we examined the efferent projections of MO and VO in the rat. Although MO and VO projections overlap, MO distributes more widely throughout the brain, particularly to limbic struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
239
4
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(266 citation statements)
references
References 122 publications
(195 reference statements)
19
239
4
4
Order By: Relevance
“…Concerning striatal connectivity, the AIC mainly projects to ventral and lateral parts of the striatum, whereas the OFC projects more dorsally and medially (Schilman et al, 2008). Concerning frontal connectivity, the AIC has major interconnections with the anterior cingulate, prelimbic, and infralimbic cortex, whereas the OFC is mainly interconnected with the anterior cingulate cortex and has much less interconnection with prelimbic and infralimbic cortex (Hoover and Vertes, 2011). The important point of our results is that AIC and OFC inactivations had opposite effects on risk preference, and this suggests, to our knowledge for the first time, that the AIC and OFC make different contributions to risky decisions.…”
Section: Opposite Roles Of Aic and Ofc In Risky Decision Makingmentioning
confidence: 98%
“…Concerning striatal connectivity, the AIC mainly projects to ventral and lateral parts of the striatum, whereas the OFC projects more dorsally and medially (Schilman et al, 2008). Concerning frontal connectivity, the AIC has major interconnections with the anterior cingulate, prelimbic, and infralimbic cortex, whereas the OFC is mainly interconnected with the anterior cingulate cortex and has much less interconnection with prelimbic and infralimbic cortex (Hoover and Vertes, 2011). The important point of our results is that AIC and OFC inactivations had opposite effects on risk preference, and this suggests, to our knowledge for the first time, that the AIC and OFC make different contributions to risky decisions.…”
Section: Opposite Roles Of Aic and Ofc In Risky Decision Makingmentioning
confidence: 98%
“…The ventral OFC is thought to bridge the medial and prefrontal cortical networks (Price, 2007), with the dorsal striatum being their primary extracortical target (Hoover and Vertes, 2011). While restricted access rats serve as a non-obese control with exposure to the diet in these studies, they do exhibit disordered feeding behaviour such that they consume most of their daily energy requirement within an hour.…”
Section: Gaba Onto Pyramidal Neurons Of the Lateral Ofcmentioning
confidence: 99%
“…Inactivation of the PrL, IL, and MO/VO may, therefore, disrupt social play behavior by interfering with cognitive flexibility and decision-making processes necessary for a proper social interaction. Studies in the past decade have found considerable anatomical (Groenewegen and Uylings, 2010;Hoover and Vertes, 2011;Vertes, 2004) and functional heterogeneity within the PFC and OFC (Chudasama et al, 2003;Gourley et al, 2010;Killcross and Coutureau, 2003;Mar et al, 2011;Peters et al, 2009). This begs the question of the exact contribution of PrL, IL, and MO/VO in social play behavior, given that their inactivation produces comparable reductions in social play.…”
Section: Importance Of the Pfc For Social Play Behaviormentioning
confidence: 99%